Target-Site and Non-target-Site Resistance Mechanisms Confer Multiple and Cross- Resistance to ALS and ACCase Inhibiting Herbicides in Lolium rigidum From Spain - Torra, Joel; Montull, José María; Taberner, Andreu; Onkokesung, Nawaporn; Boonham, Neil; Edwards, Robert (Frontiers in Plant Science, 2021)
Lolium rigidum is one the worst herbicide resistant (HR) weeds worldwide due to its proneness to evolve multiple and cross resistance to several sites of action (SoA). In winter cereals crops in Spain, resistance to acetolactate synthase (ALS)- and acetyl-CoA carboxylase (ACCase)-inhibiting herbicides has become widespread, with farmers having to rely on pre-emergence herbicides over the last two decades to maintain weed control. Recently, lack of control with very long-chain fatty acid synthesis (VLCFAS)-inhibiting herbicides has been reported in HR populations that are difficult to manage by chemical means. In this study, three Spanish populations of L. rigidum from winter cereals were confirmed as being resistant to ALS- and ACCase-inhibiting herbicides, with broad-ranging resistance towards the different chemistries tested. In addition, reduced sensitivity to photosystem II-, VLCFAS-, and phytoene desaturase-inhibiting herbicides were confirmed across the three populations. Resistance to ACCase-inhibiting herbicides was associated with point mutations in positions Trp-2027 and Asp-2078 of the enzyme conferring target site resistance (TSR), while none were detected in the ALS enzyme. Additionally, HR populations contained enhanced amounts of an orthologue of the glutathione transferase phi (F) class 1 (GSTF1) protein, a functional biomarker of non-target-site resistance (NTSR), as confirmed by enzyme-linked immunosorbent assays. Further evidence of NTSR was obtained in dose-response experiments with prosulfocarb applied post-emergence, following pre-treatment with the cytochrome P450 monooxygenase inhibitor malathion, which partially reversed resistance. This study confirms the evolution of multiple and cross resistance to ALS- and ACCase inhibiting herbicides in L. rigidum from Spain by mechanisms consistent with the presence of both TSR and NTSR. Moreover, the results suggest that NTSR, probably by means of enhanced metabolism involving more than one detoxifying enzyme family, confers cross resistance to other SoA. The study further demonstrates the urgent need to monitor and prevent the further evolution of herbicide resistance in L. rigidum in Mediterranean areas.